'All Tee, No Shade': A manifesto for a subtle critical practice negotiating queer, East Asian masculinities through T-shirts. Issue 1 (1st October 2021) - Thai, Sang
'All Tee, No Shade' is a practice-led research project that explores the use of the men's T-shirt to challenge and disrupt hegemonic subjectivities that contribute to the marginalization and discrimination of the queer Asian diaspora. Through an exploration of my pilot project of the same name, produced as part of the arts programme of Virgin Australian Melbourne Fashion Festival in 2020, I propose that norm-critical design methodologies exploring intersectional experiences of fashion and dress can produce material outcomes that challenge the discrimination and oppression associated with compounding conditions of race and sexuality. I use the notion of 'subtle' traits as a condition of the East Asian diasporic experience to reveal how race and sexuality might be expressed through fashion production to disrupt conceptions of 'otherness'. This is achieved with T-shirts that have printed graphic configurations that align with contemporary streetwear but with 'subtle' signifiers embedded through the signs and lexicons of Asian and queer communities. Using an autoethnographic approach, the work is informed by my past fashion design industry experience and reflects on racial and queer marginalization and discrimination through styling and fit. The project contributes to broader discourses aimed at decentralizing dominant narratives in fashion practice and responds to a lack of academic research into diasporic Asian experiences of dress and, more specifically, queer diasporic Asian dress.